REALIZATION OF DEMOCRATIC PRINCIPLES OF ELECTIONS IN UNIVERSAL INTERNATIONAL NORMATIVELY LEGAL ACTS - Бучин, М.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article is carried out the legal analysis of international normatively legal acts of universal character in relation to realization of democratic principles of elections. An author probes international documents, developed within the framework of UNO, for the purpose the analysis of problem of application of democratic principles of elections, as important sources of international electoral law.